Uprawnienia pasażerów lotów w przypadku odmowy przyjęcia na pokład albo odwołania lub opóźnienia lotu. Wybrane zagadnienia administracyjnoprawne, cywilno-prawne i podatkowe - Babiarz, Stefan (Kwartalnik Prawa Podatkowego, 2016)
The above article discusses selected issues connected with passengers’ rights in the scope of administrative, civil, and tax law in the event of denied boarding and of cancellation or long delay of flights. Regulation (EC) No. 261/2004 of the European Parliament and the Council of 11th February 2004 establishing common rules on compensation and assistance to passengers in the event of denied boarding and of cancellation or long delay of flights, and repealing Regulation (EEC) No. 295/91 explicitly provides for compensation to passengers only in the event of denied boarding against the will of the passenger and in case of flight cancellation. The Regulation does not explicitly provide for such compensation in the event of long delay of flights. In consideration of the case law of CJEU, conflicting judgements, and equivocal interpretations, it should be concluded that passengers should be entitled to the right to compensation also in the event of long delay of flights. The provisions of the Regulation distinguish between the right to compensation and the right to assistance. The nature of these rights and the source of their creation require assuming that these two rights are indeed of compensatory nature, and, furthermore, they constitute compensation within the meaning of civil law although they do not pose an explicit and direct loss to passengers understood as property damage. The Regulation explicitly indicates either the amount of compensation or the rules of determining the amount; however, the Regulation is not an act, and, consequently, provisions of Art. 21(1) point 3 of Personal Income Tax Act do not explicitly apply to the Regulation. However, due to the nature of the Regulation, the manner of adoption and scope of applicability, it should be treated as an act within the meaning of the referred provision, which would mean that compensation covered by the Regulation is subject to exemption from personal income tax.